Risk-seeking for losses is associated with 5-HTTLPR, but not with transient changes in 5-HT levels - Neukam, Philipp T.; Rietschel, Marcella; Witt, Stephanie (Psychopharmacology, 2018)
Serotonin (5-HT) plays a key role in different aspects of value-based decision-making. A recent framework proposed that tonic 5-HT (together with dopamine, DA) codes future average reward expectations, providing a baseline against which possible choice outcomes are compared to guide decision-making.
Gesehen am 19.11.2020